2005
DOI: 10.1016/j.actamat.2004.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and growth of the discontinuous precipitation reaction at [0 1 1] symmetric tilt boundaries in Cu–Be alloy bicrystals

Abstract: The initiation and growth of discontinuous precipitation (DP) at [011] symmetric tilt boundaries in Cu 0.75 wt% Be alloy bicrystals have been studied. Transmission electron microscopy revealed that precipitates tended to nucleate at a boundary in such a manner that their habit plane, {112} or {445} , with one of the adjoining grains lay as close as possible to the boundary. The habit plane with a low energy formed on both sides of the precipitates behind an initially migrating boundary, indicating the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
3
16
1
1
Order By: Relevance
“…About 50 grain boundaries in each of the Cu-Be-Co and 0.01 and 0.03%Mg-added alloys aged at 320°C for 30 min were observed using TEM. Similar to our previous observation [13], precipitation of the phase took place first at grain boundaries and then the boundaries migrated. DP cells were formed for about 100, 80 and 50% of the boundaries examined in the Cu-Be-Co and 0.01 and 0.03wt.%Mg-added alloys, indicating that the addition of Mg suppresses the formation of cells.…”
Section: Effect Of Mg On Strengthsupporting
confidence: 70%
See 1 more Smart Citation
“…About 50 grain boundaries in each of the Cu-Be-Co and 0.01 and 0.03%Mg-added alloys aged at 320°C for 30 min were observed using TEM. Similar to our previous observation [13], precipitation of the phase took place first at grain boundaries and then the boundaries migrated. DP cells were formed for about 100, 80 and 50% of the boundaries examined in the Cu-Be-Co and 0.01 and 0.03wt.%Mg-added alloys, indicating that the addition of Mg suppresses the formation of cells.…”
Section: Effect Of Mg On Strengthsupporting
confidence: 70%
“…The first critical step of the DP reaction in Cu-Be alloys is heterogeneous grain 7 boundary nucleation [12,13]. About 50 grain boundaries in each of the Cu-Be-Co and 0.01 and 0.03%Mg-added alloys aged at 320°C for 30 min were observed using TEM.…”
Section: Effect Of Mg On Strengthmentioning
confidence: 99%
“…The first critical step of the DP reaction in Cu-Be alloys is heterogeneous grain-boundary nucleation [11,12]. Similar to our previous observation [12], boundary precipitation of the γ phase occurred before any significant boundary migration.…”
Section: Precipitation Morphologysupporting
confidence: 75%
“…The DP cell in Cu-Be alloys consists of lamellae of the equilibrium γ phase (CuBe intermetallic) and solute-depleted α phase (Cu-rich solid solution). Rod-shaped precipitates of the γ phase in DP cells exhibit an orientation relationship to Cu matrix of the α phase [10][11][12]. We have found that the growth rate of DP cells depends on the sense (tension or compression) of the applied stress, and the growth rates in the loading and the transverse directions are identical, different from the previous observations [3,4,6,7,9].…”
Section: Introductioncontrasting
confidence: 55%
“…The dependence between misorientation angle and incubation period and cell growth velocity for the DP reaction at [011] symmetric tilt boundaries in Cu-0.75wt% Be alloy bicrystals was studied by Monzen [37] using TEM technique. Lower-energy boundaries were found to exhibit a longer incubation period and a slower growth rate.…”
Section: Relation To Gb Orientationmentioning
confidence: 99%